IMPLEMENTASI PENDEKATAN TARL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN BAHASA INDONESIA - Susanti, Nila Dwi; Amin, Siti Maghfirotun; Muawanah, Muawanah; Indrati, Joeli; Idayati, Nurul (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
Factors that influence low student learning outcomes due to less interactive learning activities and lack of variation in approaches, methods, and learning media applied in the classroom, teachers need to innovate by making improvements to improve student learning outcomes through learning with the Teaching at the right level (TaRL) approach. The method used in this study is the Classroom Action Research (CAR) method. This study was conducted in two cycles, each cycle consisting of four stages according to the Kemmis model, namely planning, acting, observing, and reflecting. Based on the results of the study, it can be concluded that the application of the TaRL approach to improve student learning outcomes can run well and is said to have been successful. This is evidenced by the results of observations of teacher activities in cycle I which reached 76% then increased in cycle II to 96%. Likewise, the results of student observations in cycle I reached 78% and increased significantly in cycle II to 90%. The learning outcomes of class IV-B students at SDN Margorejo VI/524 Surabaya experienced a very significant increase. This is proven based on the percentage of student learning outcomes completion which was 44% in the pre-cycle, then increased after the cycle I actions were carried out to 60%, and increased to 84% in cycle II.